Effects of future climate on suitability of major crops in Eastern Kansas River Basin - Rintu Sen; Vaishali Sharda; Zachary T. Zambreski; Ikenna Onyekwelu; Katherine S. Nelson (Journal of Water and Land Development)
Climate change significantly threatens food security and the agricultural economy, particularly under rainfed conditions. This study uses the Decision Support System for Agrotechnology Transfer (DSSAT) crop simulation model to evaluate the future suitability of growing maize and soybean in the Eastern Kansas River Basin (EKSRB) under two projected climate scenarios (RCP 4.5 and RCP 8.5) from 2006 to 2099. By comparing the baseline (1990–2019) and future climates, the yield gap percentage method is employed to quantify the discrepancy between actual and potential yields. This innovative approach integrates spatial soil variability and advanced climate projections from 18 global climate model (GCMs), enhancing the accuracy of crop suitability assessments. Results indicate yield losses ranging from 23% to 57% for maize and 20% to 36% for soybean, with maize experiencing a greater yield gap than soybean, highlighting soybean’s resilience under future climatic conditions. The study identifies critical regions within the EKSRB where adaptive strategies are most needed and provides insights for policymakers to develop targeted agricultural strategies, facilitate policy planning, and select mitigation strategies for vulnerable areas. This research underscores the necessity for adaptive agricultural practices to ensure food security and sustainability, offering a robust framework that can be adapted to similar regions globally.